2018
DOI: 10.21470/1678-9741-2017-0071
|View full text |Cite
|
Sign up to set email alerts
|

Selenium, Vitamin C and N-Acetylcysteine do not Reduce the Risk of Acute Kidney Injury after Off-Pump CABG: a Randomized Clinical Trial

Abstract: ObjectiveThe aim of this study was to investigate the impact of perioperative administration of N-acetylcysteine, selenium and vitamin C on the incidence and outcomes of acute kidney injury after off-pump coronary bypass graft surgery.Methods291 patients requiring elective off-pump coronary bypass graft surgery were randomized to receive either N-acetylcysteine, vitamin C and selenium 600 mg, 1500 mg, 0.5 mg, and nothing orally twice a day, respectively, from the day before to 2 days after surgery. They were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 32 publications
2
44
1
Order By: Relevance
“…The proportion of males varied from 58% to 75%. Five trials were carried out in Iran [12,13,15,18,19], two in Egypt [14,16], one in the USA [11], and one in Japan [17]. For detailed descriptions of the trials, see Additional file 1: Table S1.…”
Section: Results Of the Included Trialsmentioning
confidence: 99%
See 4 more Smart Citations
“…The proportion of males varied from 58% to 75%. Five trials were carried out in Iran [12,13,15,18,19], two in Egypt [14,16], one in the USA [11], and one in Japan [17]. For detailed descriptions of the trials, see Additional file 1: Table S1.…”
Section: Results Of the Included Trialsmentioning
confidence: 99%
“…For detailed descriptions of the trials, see Additional file 1: Table S1. The Amini trial [12] results are modified as described previously [1] *Estimated vitamin C dose, see the "Methods" section **Sadeghpour et al [19] recruited 500 participants but reported the results for just 290 participants [1]. Because of the high dropout rate (42%), we did not include this trial in our calculations, but we overlay the findings in Fig.…”
Section: Results Of the Included Trialsmentioning
confidence: 99%
See 3 more Smart Citations